Cigarette smoking and acute eosinophilic pneumonia: insights from a case series of 17 patients - I Re Heo; Tae Hoon Kim; Kyung Nyeo Jeon; Ho Cheol Kim (Kosin Medical Journal)
Background Acute eosinophilic pneumonia (AEP) is a rare and severe lung condition characterized by a rapid accumulation of eosinophils in the alveoli, leading to respiratory distress. This study analyzed the clinical characteristics of affected patients, aiming to shed light on the relationship between cigarette smoking and AEP. Methods This retrospective study analyzed 17 cases of AEP, focusing on patients' smoking habits, clinical symptoms, diagnostic findings, and treatment outcomes. Data were collected from medical records, imaging studies, and bronchoalveolar lavage (BAL) findings. Results The study cohort consisted primarily of male military personnel (94.1%), with a mean age of 20.8 years. Symptoms generally appeared approximately 2.82 days prior to hospitalization, with a mean body temperature at admission of 37.6 °C. The mean initial peripheral blood white blood cell count was 15.3×103/μL, with eosinophil percentages starting at 0.2%, peaking at a mean of 16.1%, and reaching as high as 32.4%. BAL fluid analysis showed a mean eosinophil level of 46.6%±15.1% (range, 17%–67%). In most cases, radiological examinations revealed bilateral ground-glass opacities, interlobular septal thickening, various degrees of airspace consolidation, and bilateral pleural effusions. Steroid treatment was administered to 70.5% of patients, lasting a mean of 8.3 days and resulting in significant improvements. Conclusions These cases reinforce the strong link between cigarette smoking and AEP. Additionally, these cases demonstrate the importance of obtaining a detailed smoking history and thorough diagnostic assessments, including BAL, in order to facilitate a more rapid diagnosis and early initiation of corticosteroid treatment.